Colour identification of sterilized and unsterilized oil palm fruitlet mesocarp - Wondi, Mohd Hafizz; Shamsudin, Rosnah; Yunus, Robiah (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
This study was carried out to compare sterilized and unsterilized oil palm fruitlet in terms of its mesocarp fibre CIE Lab colour after exposure to environment during storage time using instrumental method. The colour of mesocarp is an important parameter which reflects the level of oxidation occurred and thus the quality of oil extracted. The fruitlet was cut to specific dimension and exposed to the environment for a few days to induce natural oxidation. Then, the colour distribution (in terms of L*, a* and b* values) of exposed surface was measured using Konica Colour Reader. The individual parameters of L*a*b* color systems were evaluated daily for three days. The smallest change of colour parameter was observed on sterilized fruitlet and biggest colour change occurred on unsterilized fruitlet. These findings indicate that more intense oxidation took place in unsterilized fruitlet. This proves that sterilization process will stop further damage towards the oil palm fruitlet due to oxidation. In summary, the colour difference between sterilized and unsterilized fruitlet colour after exposure to environment were conducted in order to prove the occurrence of oxidation. The results will be useful in palm oil industry specifically to develop a proper palm freshness evaluation system during grading.